2016
DOI: 10.1016/j.ymeth.2016.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Practical guide for dynamic monitoring of protein oxidation using genetically encoded ratiometric fluorescent biosensors of methionine sulfoxide

Abstract: In cells, physiological and pathophysiological conditions may lead to the formation of methionine sulfoxide (MetO). This oxidative modification of methionine exists in the form of two diastereomers, R and S, and may occur in both free amino acid and proteins. MetO is reduced back to methionine by methionine sulfoxide reductases (MSRs). Methionine oxidation was thought to be a nonspecific modification affecting protein functions and methionine availability. However, recent findings suggest that cyclic methionin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…This notion, as well as previous measurements of methionine oxidation conducted on oxidatively stressed proteomes, suggested that global levels of methionine oxidation may be moderately high and broadly distributed . However, previous attempts at quantifying global levels of in vivo methionine oxidation in unstressed cells have relied on the use of reporter molecules and antibodies with low specificity. , These approaches may not provide an accurate census of levels of methionine oxidation and do not allow for the quantification of the distribution of methionine oxidation across a diverse array of methionine-containing protein sequences. Here, we were able to quantify >3800 chemically distinct methionine-containing peptides in their native context across two biological replicates with ∼1000 peptides shared between them.…”
Section: Discussionmentioning
confidence: 99%
“…This notion, as well as previous measurements of methionine oxidation conducted on oxidatively stressed proteomes, suggested that global levels of methionine oxidation may be moderately high and broadly distributed . However, previous attempts at quantifying global levels of in vivo methionine oxidation in unstressed cells have relied on the use of reporter molecules and antibodies with low specificity. , These approaches may not provide an accurate census of levels of methionine oxidation and do not allow for the quantification of the distribution of methionine oxidation across a diverse array of methionine-containing protein sequences. Here, we were able to quantify >3800 chemically distinct methionine-containing peptides in their native context across two biological replicates with ∼1000 peptides shared between them.…”
Section: Discussionmentioning
confidence: 99%
“…While some proteins use reversible thiol modification as mechanism to regulate their activity, others undergo reversible oxidation of critical methionine residues (Manta and Gladyshev, 2017). However, since precise quantification of the extent of in vivo methionine oxidation in proteins is still challenging, it is unclear how many proteins and pathways use reversible methionine oxidation as their mode of redox control (Peterfi et al, 2016).…”
Section: Redox Regulation: Controlling Protein Function During Oxidatmentioning
confidence: 99%
“…While dozens of proteomic papers reported on the identification and quantification of sulfenic acids, disulfides and persulfides in proteins 4145 , few reports targeted formation of MetO in vivo and, if they did, studies focused on cells subjected to high (non-physiological) concentrations of H 2 O 2 or chloramines 19,46 . In this regard, future studies may benefit from the use of novel highly sensitive proteomic techniques 47 as well as the utilization of genetically-encoded biosensors for MetO (MetROX and MetSOX) 48,49 .…”
Section: Oxidation Of Methionine: Where When and How?mentioning
confidence: 99%